Immunotherapy in ovarian cancer: fake news or the real deal?. Issue 1 (January 2019) - Marth, Christian; Wieser, Verena; Tsibulak, Irina; Zeimet, Alain G
Abstract : Cancer immunotherapy has emerged as one of the most promising approaches in oncology, and comprises the activation of the immune system to induce tumor immune surveillance or to reverse the tumor immune escape. Different therapeutic strategies for ovarian carcinoma have evolved over the years. Already 30 years ago, the first clinical studies focused on modulating the tumor cytokine network with special attention to interferon-mediated immune responses. With the exploration of specific tumor antigens such as NY-ESO-1, which is expressed in ovarian carcinoma and other malignancies, the development of therapeutic cancer vaccines has been pursued initiating the era of personalized anti-cancer medicine. Almost at the same time, the adoptive transfer of genetically modified autologous tumor-reactive T-cells occurred, but response rates in ovarian carcinoma were disappointing. Today, probably the most promising therapeutic approach in this context is the blockade of immune checkpoints, such as programed cell death protein 1 (PD-1) and one of its ligands (PD-L1) or cytotoxic T-cell lymphocyte-associated antigen 4 (CTLA-4), which has demonstrated impressive response rates in malignant melanoma and non-small cell lung cancer. Despite increasing availability of treatment approaches that target tumor immune surveillance in ovarian carcinoma, selecting patient groups that particularly benefit from these treatment modalities is clinically challenging as predictive biomarkers are lacking. Here, we summarize different immunotherapy approaches in ovarian cancer and discuss why immunotherapy in ovarian cancer is still in its infancy.